Hadits-Hadits Tentang Perintah Kewajiban Mendidik Dan Berpendidikan - Saleh Adri; Harli Harli (Pusdikra Publishing, 2022)
This study aims to examine the Hadiths Concerning the Obligation to Educate and Be Educated. The research method using library techniques is library research carried out by reading, studying and recording various literature or reading materials that are appropriate to the subject matter, then filtered and outlined in a theoretical framework. The results of the research in the form of educating laws are mandatory. The argument is in one hadith from Abu Daud No. 495. Education is also mandatory. Based on the hadith of Sunan Ibn Majah no. 224. Education is very important, based on the hadith of Sahih Bukhari no. 100. There are many other hadiths which state about the obligation to educate and be educated, with the limitations of this paper, I will suffice only 3 hadiths.